Cashmere Production from Maraz Goats - O.Aziz, Kasim (Sulaimani Journal for Pure and Applied Sciences, 2009)
Cashmere/down production of 118 Maraz goats (36 males and 82 females) aged one to five years and older was investigated. Evaluation was based on the down percentage in undercoat. The overall mean of live weight, fleece weight, down percentage, fiber diameter and fiber length were 26.8 kg, 699.7 g, 27.7 %, 22.5 μm and 57.7 mm, respectively. Live weight, fleece weight and down percentage were significantly heavier in males than in females. Age affects significantly all studied traits except the fiber length. The effect of interaction between age and sex was significant on most of the studied traits. Correlations among traits were also studied. Possibilities of increasing the cashmere production of Maraz goats in Iraqi-Kurdistan by genetic improvement through selection and improved management are considered.
Keywords: Maraz goat; Body weight; Cashmere quality